Comparison of single copy gene‑based duplex quantitative PCR and digital droplet PCR for monitoring of expansion of CD19‑directed CAR T cells in treated patients - Schubert, Maria-Luisa; Berger, Carolina; Kunz, Alexander; Schmitt, Anita; Badbaran, Anita; Neuber, Brigitte; Zeschke, Silke; Wang, Lei; Riecken, Kristoffer; Hückelhoven-Krauss, Angela; Müller, Ingo; Müller-Tidow, Carsten; et al. (International journal of oncology, 2022)
Chimeric antigen receptor (CAR) T cell therapy with axicabtagene ciloleucel, tisagenlecleucel and brexucabtagen ciloleucel has been adopted as the standard of care for patients with refractory and/or relapsed CD19‑positive lymphoid malignancies. Monitoring of kinetics of CAR T cells after administration is crucial for patient follow‑up and important to guide clinical decisions for patients subjected to CAR T cell therapy. Information of transgene copies within a CAR T cell product prior to administration, i.e. vector copy numbers, is of high importance to warrant patient safety. However, experimental assays for quantitative CAR T cell monitoring in the open domain are currently lacking. Several institutions have established in‑house assays to monitor CAR T cell frequencies. In the present study, the quantitative (q)PCR assay established at the Heidelberg University Hospital (Heidelberg, Germany), i.e. single copy gene‑based duplex qPCR, was compared with the digital droplet PCR assay established at the University Medical Center Hamburg‑Eppendorf (Hamburg, Germany). Both methods that were independently developed enable accurate and comparable CAR T cell frequency assessment and are useful in the clinical setting.